Simultaneous Analysis of Seismic Velocity and Electrical Conductivity in the Crust and the Uppermost Mantle: A Forward Model and Inversion Test Based on Grid Search. Issue 9 (27th September 2021) - Iwamori, Hikaru; Ueki, Kenta; Hoshide, Takashi; Sakuma, Hiroshi; Ichiki, Masahiro; Watanabe, Tohru; Nakamura, Michihiko; Nakamura, Hitomi; Nishizawa, Tatsuji; Nakao, Atsushi; Ogawa, Yasuo; Kuwatani, Tatsu; et al.
Abstract: This study presents a forward model to quantify the P‐wave velocity ( V P ), S‐wave velocity ( V S ), and electrical conductivity ( σ ) of the solid‐liquid mixtures for a given set of pressure, temperature, lithology, liquid phase (aqueous fluid or melt), liquid fraction, and geometrical parameters in relation to the aspect ratio and connectivity of the liquid phase. This is based on previous experimental and theoretical studies on seismic velocity and electrical conductivity of solid rocks and liquid phases. A total of 78 lithologies, an aqueous fluid with NaCl (∼0–10 wt.%), and mafic to felsic melt appropriate for the crust and the uppermost mantle conditions were described in terms of V P, V S, and σ, as per previous experimental measurements and molecular dynamics simulation. This forward model is provided as a Windows executable program, and generates synthetic V P, V S, and σ, referring to the seismic velocities and electrical conductivity observed in the northeast Japan arc. After generation of the synthetic V P, V S, and σ, the original lithology and liquid parameters (phase, fraction, aspect ratio, and connectivity) were searched by implementing the grid search algorithm to map the misfit over the broad parameter space. The mapping shows the presence of a global misfit minimum around the optimized solution and the possibility of resolving the lithology and the liquid phase parameters based on the observed V P, V S, and σ by using the forward model presented in this study. Plain Language Summary: Liquid phases such as aqueous fluid and magma present within the solid Earth play crucial roles in various geodynamic processes including earthquake and volcanic eruption, as well as in the evolution of our planet. This study aims to improve the subsurface imaging of the potentially variable types of liquid phase and solid rock, based on the near‐surface observations concerning seismic velocity and electrical conductivity of the Earth's interior. We constructed a quantitative model to predict the physical properties of liquids and rocks. Then we used the model to perform "inversion, " which estimates the physical properties of liquid and rock based on the observed seismic velocity and electrical conductivity. The inversion test using synthetic data shows the utility of our model. Key Points: A forward model is presented to quantify seismic velocity and electrical conductivity of solid‐liquid mixtures in crust‐uppermost mantle The input parameters include pressure, temperature, lithology, liquid phase composition and fraction, and solid‐liquid geometry For a given set of seismic velocity and electrical conductivity, the optimal parameter values can be found by inversion